The effect of binder’s durability on the performance of asphalt mixture - Tan, Albert Yee Hau (Nanyang Technological University, 2020)
As of the end of 2014, there are 3496 km length of asphalt pavement according to Land Transport Authority, therefore the maintenance and rehabilitation of asphalt pavement can contribute to a considerable portion of national budget. By improving the durability of pavement, the cost reduction and the riding quality of pavement can be optimised. One of the major influencing factors on the durability of asphalt pavement is the quality of binder. Herein, the objective of this project is to study the effects of binder durability on the performance of asphalt pavement. In this project, two different grades of binder (60/70 and C320) were aged by Pressurised Ageing Vessels (PAV) to two different degrees of aging which are referred as moderately aged (10hours) and highly aged (20hours). Next, mixture specimens were cast using the six different binders (including unaged binders) by means of gyratory compactor. A total of 54 cylindrical specimens were tested on three mechanistic tests which are creep resistance test, indirect tensile test (IDT) and moisture susceptibility test. From the results, it is observed that the aged binder can improve the rutting resistance based on the creep resistance test. While for IDT, the degree of ageing of binder did not have any significant impact on the resilient modulus. On the other hand, the impact of ageing on moisture-induced damage was observed but not substantively. It could be deduced from the analysis that the effects of binder durability is more prominent on some aspects only. Herein, more studies on other aspects of pavement durability are required to provide a definitive and comprehensive conclusion.